2008
DOI: 10.1177/0885412208322921
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Complexities of Annexation

Abstract: Annexation is the most common and frequent type of local boundary adjustment. It is a complex process with significant implications for communities. This article summarizes past and recent scholarly research relating to the state requirements guiding annexation, and the fiscal impacts, local motivations, and social and political implications of the process. Its purpose is to integrate literature from across disciplines to better understand the many dimensions of annexation and the challenges that confront plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
29
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 39 publications
(58 reference statements)
0
29
0
3
Order By: Relevance
“…Total net expenditures captures municipal management decisions (Molotch, 1976, p. 309;CASCo). County persons per housing unit (household population/occupied housing units) captures the transformation (fiscal, population) of unincorporated areas (Edwards, 2008;Heim, 2012;CADoF). 23 City area in square miles, adjacent to central city, and distance from central city (i.e., straight-line distance between the central and noncentral city halls) measure spatial components (SCAg and SACog).…”
Section: Datamentioning
confidence: 99%
“…Total net expenditures captures municipal management decisions (Molotch, 1976, p. 309;CASCo). County persons per housing unit (household population/occupied housing units) captures the transformation (fiscal, population) of unincorporated areas (Edwards, 2008;Heim, 2012;CADoF). 23 City area in square miles, adjacent to central city, and distance from central city (i.e., straight-line distance between the central and noncentral city halls) measure spatial components (SCAg and SACog).…”
Section: Datamentioning
confidence: 99%
“…Edwards () offered the most comprehensive literature review on the complexity of annexation. Edwards showed that historically annexation has been pursued to offset the fiscal stress caused by the migration of middle and upper‐income people fleeing central cities.…”
Section: Previous Research On Land Use Regulations and Annexationmentioning
confidence: 99%
“…Son objet est moins de suivre scrupuleusement l'évolution des différents tracés municipaux, qui a peu d'intérêt en soi, que de comprendre les annexions et redécoupages multiples de la carte municipale allemande comme un processus politique et territorial, faisant l'objet de contestations (Edwards, 2008) et visant des objectifs non seulement fiscaux mais également symboliques et territoriaux et contribuant à l'émergence de villes de plus en plus étalées et de moins en moins denses.…”
unclassified
“…L'ambition à l'oeuvre derrière ces différentes annexions n'est souvent pas prioritairement démographique, même si le lien entre croissance de la population et réagencement des frontières municipales par fusions est relativement logique (Rice et al, 2014). Dans les cas américains comme européens, les annexions et fusions de diverses natures sont davantage guidées par des considérations fiscales (Cho, 1969) ou de contrôle de l'usage des sols (Fischl, 2001) : les annexions sont ainsi considérées comme un des outils importants à la disposition des responsables de planification stratégique à l'échelle régionale pour pouvoir contrôler l'étalement urbain (Edwards, 2008).…”
unclassified
See 1 more Smart Citation